Antiviral treatment with fluoxetine for rituximab‐associated chronic echovirus 13 meningoencephalitis and myofasciitis. (17th July 2022) - Vermeersch, Gaël; Laenen, Lies; Lens, Géraldine; van der Elst, Kim C. M.; Thal, Dietmar Rudolf; Jentjens, Sander; Demaerel, Philippe; Van Nieuwenhuyse, Tine; Wollants, Elke; Boeckx, Nancy; Verhaert, Nicolas; Dubois, Benedicte; et al.
Abstract: Background and purpose: Enterovirus infections pose a serious threat for patients with humoral deficiencies and may be lethal, whilst the efficacy of proposed treatment options such as corticosteroids, intravenous immunoglobulins and fluoxetine remains debated. Methods: Viral clearance was investigated in a patient with rituximab‐induced B‐cell depletion and chronic echovirus 13 (E13) meningoencephalitis/myofasciitis in response to intravenous immunoglobulins and fluoxetine using sequential semi‐quantitative E13 viral load measurements by real‐time reverse transcription polymerase chain reaction. Fluoxetine concentrations in plasma and cerebrospinal fluid were determined by liquid chromatography mass spectrometry. Results: Intravenous immunoglobulins appeared ineffective in this case of E13 infection, whereas virus clearance in cerebrospinal fluid was obtained after 167 days of oral fluoxetine. Since treatment with corticosteroids resulted in a flare of symptoms, rechallenge with viral load measurements was not attempted. Conclusion: In this report of a patient with rituximab‐associated chronic echovirus 13 meningoencephalitis, viral clearance in response to single treatment options is assessed for the first time. Our observations further support the in vivo efficacy of fluoxetine against enteroviral infections. More research is needed to establish its efficacy in different enterovirus strains. Abstract : In this report of a patient with rituximab‐associated chronic echovirus 13 (E13) meningoencephalitis, viral clearance in response to single treatment options is assessed for the first time. Our observations further support the in vivo efficacy of fluoxetine against enteroviral infections. Oral fluoxetine treatment was associated with clinical improvement and molecularly confirmed E13 clearance from cerebrospinal fluid after 167 days.